Humanism and Nationalism in the Sports Arena: Uniting Differences, Building Peace - Novian, Geraldi; Komarudin, Komarudin; Rismayadi, Alen; Nursaba, Siti; Zahra, Sabrina Khalisatu (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2025)
Sport is not just a physical activity or a means of winning medals, but has now evolved into a socio-political instrument capable of addressing the roots of inequality, conflict, and even humanitarian crises. This article critically examines how Sport for Development and Peace (SDP) is used as a social intervention strategy in marginalized communities globally, although it is not immune to criticism for the reproduction of power relations and neo-colonialism in practice. Phenomena such as the participation of refugee athletes in the 2016 Rio Olympics or the unification of the two Koreas under one flag reflect the potential of sport as a medium for soft diplomacy and a rare but meaningful symbol of reconciliation. Domestically, Indonesia with its diversity of ethnicities, religions, and identities has strong assets to utilize sport as a national unifier and a symbol of social cohesion. Furthermore, the public health crisis, both physical and mental, emphasizes the urgency of sport as a preventative solution. Data from the WHO and the Ministry of Health show a surge in non-communicable diseases and mental disorders that can be reduced through active participation in sport. However, the challenge is not simply participation, but rather a restructuring of the development paradigm: from sport for development to development through sport. This article emphasizes that the state must be present, not merely as a facilitator, but as a strategic policy director that makes sport an integrative pillar between development, nationalism, diplomacy, and humanism. Without it, sport will be merely a temporary stage, not an agent of change.